Influence of Si on microstructure and mechanical properties of TiAISiN hard thin films - Nakonechna, O.I.; Zakharenko, M.I. (Functional Materials, 2004)
Structural and mechanical properties of nanocomposite TiAI(Si)N thin films prepared using arc-plasma PVD deposition technique on WC-Co substrates have been characterized by X-ray diffraction and nanoindentation. TEM have been used to study the microstructure of thin films, in order to understand the growth mechanism thereof. The maximum hardness of thin films was observed for materials of near the Al-Si eutectic composition. The smallest grain size (30 nm) in the film corresponds also to that composition. Методами рентгеновского фазового анализа и наноиндентирования исследованы структурные и механические свойства нанокомпозитных тонких пленок на основе TiAISiN. Материалы получены методом катодного осаждения на подложку WC-Co. Для выяснения механизма роста тонких пленок проведены электронно-микроскопические исследования. Обнаружено, что максимальная твердость тонких пленок наблюдается для материалов с химическим составом вблизи области эвтектики Al-Si. Также этому составу соответствует наименьший размер кристаллита в пленке (30 нм). Методами рєнтгєнівського фазового аналізу та наноіндентування досліджєно структуру та механічні властивості нанокомпозитних тонких плівок на основі TiAISiN. Матеріали одержано методом катодного осадження на підкладку WC-Co. З метою визначення механізму росту тонких плівок проведено електронно-мікроскопічні дослідження. Максимальна твердість плівок спостерігається для зразків, хімічний склад яких знаходиться поблизу області евтектики AI-Si. Цьому складу відповідає також і мінімальний розмір кристалітів (30 нм).